ISI PESAN DAN KREATIVITAS IKLAN SHOPEE VERSI "PAK JOKOWI BAGI-BAGI SEPEDA" - Masrurul Laily (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2018)
This research aims to find advertisers' creativity and find out about the content of messages contained in shopee advertisements, "Pak Jokowi's share of bicycles". In this journal we will make observations through qualitative methods by observing through semiotics according to Roland Barthes contained in the ad and some observations about the storyline, atmosphere and body language. So that the reader will find out whether the stories that Shopee's ad creators are made are excessive and even inappropriate or vice versa. The results of this study indicate that shopee ads are very entertaining and the content of the message reaches the viewers. According to Barthes' semiotics method, the markers used also understand the viewers who are watching, as well as interesting or not, this ad is very, very interesting and easily remembered by viewers.